A TOUR THROUGH THE DOCTRINARY EVOLUTION OF THE ACADEMIC TEACHING OF PHILOSOPHY IN LAW IN COSTA RICA - Cordero Molina, Sofia (2026)
Philosophy has accompanied the curricular framework of the law career since the dawn of its academic teaching